2021
DOI: 10.1042/bcj20210202
|View full text |Cite
|
Sign up to set email alerts
|

Importance of tyrosine phosphorylation for transmembrane signaling in plants

Abstract: Reversible protein phosphorylation is a widespread post-translational modification fundamental for signaling across all domains of life. Tyrosine (Tyr) phosphorylation has recently emerged as being important for plant receptor kinase (RK)-mediated signaling, particularly during plant immunity. How Tyr phosphorylation regulates RK function is however largely unknown. Notably, the expansion of protein Tyr phosphatase and SH2 domain-containing protein families, which are the core of regulatory phospho-Tyr (pTyr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 120 publications
(212 reference statements)
0
10
0
1
Order By: Relevance
“…Although there are no typical tyrosine kinases identified in plants, some plant RLKs are capable of tyrosine phosphorylation (Bojar et al, 2014). Phospho-proteomics data show that the relative abundance of phosphorylated tyrosine residues in plants is similar to that in animals (Ahsan et al, 2020;M€ uhlenbeck et al, 2021), hereby indicating the important role that tyrosine phosphorylation plays in signalling events in plants. Thus, the role of plant PTPs is probably largely underestimated, and furthermore, how plant PTPs are actually activated remains unknown.…”
Section: Introductionmentioning
confidence: 86%
“…Although there are no typical tyrosine kinases identified in plants, some plant RLKs are capable of tyrosine phosphorylation (Bojar et al, 2014). Phospho-proteomics data show that the relative abundance of phosphorylated tyrosine residues in plants is similar to that in animals (Ahsan et al, 2020;M€ uhlenbeck et al, 2021), hereby indicating the important role that tyrosine phosphorylation plays in signalling events in plants. Thus, the role of plant PTPs is probably largely underestimated, and furthermore, how plant PTPs are actually activated remains unknown.…”
Section: Introductionmentioning
confidence: 86%
“…All the identified 57 kinases possess both the Ser/Thr-specificity motifs in subdomains VI and the Tyr-specificity motifs in subdomain XI, suggesting that all of these kinases belong to a DsPTK family [ 8 ]. Recent studies have shown that many important plant receptor-like kinases (RLKs), sharing similar architectures with metazoan RTKs, exhibited the dual-specificity kinase activities, indicating that the Tyr phosphorylation is also an important regulatory mechanism in plants [ 19 , 26 ]. A recent in silico analysis in rice genome developed by Allimuthu et al identified 18 DsPTKs which share >80% identity within the conserved sequences of subdomains VI, VIII, and XI with the Arabidopsis Brassinosteroid-Insensitive1 (BRI1) [ 27 ], a cell surface-localized leucine-rich repeat (LRR) RLK that functions as the BR receptor [ 28 ].…”
Section: Ptks and Dual-specificity Ptksmentioning
confidence: 99%
“…The “writer” and “eraser” functions are fulfilled by DsPTKs and PTPs/DUSPs in plant cells, respectively. It was well-known that the “reader” proteins in mammals can specifically recognize and bind certain pTyr residues on target proteins to propagate the phosphorylation in a wide range of signaling pathways [ 19 ]. It would be a challenging task to find plant-specific “reader” proteins or “reader” motifs important to regulate many phosphorylation-mediated signaling processes in plants.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…All PTPases possess a signature motif of 11 amino acids at the active site (I/V)HCXAGXXR(S/T)G, which contains the cysteine (Cys) catalytic residue (indicated in bold) involved in the formation of a phosphoenzyme intermediate during the reaction (Guan and Dixon, 1991). Tyr phosphorylation and consequently Tyr dephosphorylation have recently emerged as important mechanisms for transmembrane signaling in plants, in particular in immunity processes (Mühlenbeck et al, 2021).…”
Section: Introductionmentioning
confidence: 99%